Youth information - seeking behavior - Chelton, Mary; Cool, Collen (Lanham: The Scarecrow Press, 2004)
Contents: Information - seeking behaviors of children using electronic information services during the early years 1980-1990. Studen learning in the library. Learning and the library digital. Do scribes learn?. Composing boolean search statements
Incluye referencias bibliográficas
Keywords: Information retrieval